Minat Penggunaan Terhadap Penggunaan Sesungguhnya Quick Response Code Indonesia Standard (Qris) Di Era New Normal - Dewi Kusuma Wardani; Anggi Nofita Sari (Jurnal Simki Economic, 2023)
This study was conducted with the aim of testing the effect of interest in using the actual use of QRIS. The data in this study were obtained from 100 respondents from the University of Sarjanawiyata Tamansiswa using descriptive quantitative methods and using primary data. The sample in this study was obtained using a snowball sampling technique. The results of this study indicate that interest in using has a positive effect on the actual use of QRIS